AMERICAN POLICY FOR THE REPATRIATION OF UN PRISONERS OF WAR DURING THE KOREAN WAR - Ospanov Н.М. (Journal of Oriental Studies, 2024)
In the Korean War (1950-1953), the UN armed forces took an active part in the war with the American military command on the side of the South Koreans, and Chinese people’s volunteers took an active part in the side of the North Koreans. During the fighting, tens of thousands of soldiers on both sides ended up in prison camps. Negotiations for the exchange of prisoners of war were complicated by differences in the number of prisoners of war and the presence of those who refused to repatriate to North Korea and China. In December 1951, the UN military provided a list of prisoners of war with 132,474 people, and the North Korean side - 11,559 people. However, the DPRK Army High Command initially stated that the number of South Korean prisoners of war exceeded 100,000. Accordingly, the UN military demanded an explanation from the North Korean side regarding the “disappearing South Korean prisoners of war.” A more serious issue in the negotiations was North Korea’s denial of International Committee of the Red Cross access to prisoner-of-war camps for observation. The UN forces and North Korea could not agree on the terms of the exchange for a long time. UN commanders advocated "voluntary repatriation", which took into account the individual wishes of prisoners of war, while North Korea sought to return all prisoners of war to their homeland. After repeated delays regarding the principle of repatriation, the parties agreed on the timing and principles of the exchange. However, the administration of President Syngman Rhee opposed the extradition of anti-communist North Koreans. On June 18, 1953, South Korean authorities helped free about 27,000 Korean prisoners of war from prison camps. Keywords: Korean War, prisoners of war, repatriation, UN.